Effect of Various Compositions of Vegetable Insecticide Powder on the Development of "Callosobruchus Chinensis L" and Germination Power in Mung Bean Seeds (Vigna Radiata L.) - Suzatmika, Istinan Yang; Mulya, Agus Surya; Turmuktini, Tien (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
Experimental research conducted at the office of the Sub-Unit of Pest and Disease Control Laboratories, Kalijati District, Subang Regency. The altitude of 76-100 m above sea level was carried out from March to July 2021. This study aimed to determine the effect of various compositions of vegetable insecticide powders (turmeric, pepper, Javanese chili) on the development of Callosobruchus chinensi L. and the germination of mung bean (Vigna radiata L.) seeds. ). environmental design using a completely randomized design (RAK) basic pattern, consisting of A = no powder/control; B= Turmeric; C= Pepper, D = Chili Java; E= Turmeric+Pepper; F= Turmeric + Javanese Chili; G = Pepper + Chili Java; H = Turmeric + Pepper + Chili Java ; I = Synthetic Insectica. The results showed that the combination of botanical insecticides had a significant effect on mortality at 7 DAP and, the number of eggs aged 7 DAP, 21 DAP, and 35 DAP, the number of imago, the number of larvae, the number of pupae, the percentage of seed damage, the percentage of seed weight and germination. The use of plant-based insecticides in general emphasizes the development of Callosobrucus chinensis L on the observation of mortality at the age of 7 DAP and, the number of eggs aged 7 DAP, 21 DAP, and 35 DAS, the number of imago, the number of larvae, the number of pupae as well as suppressing the level of damage to seeds, seed weight and germination